2012
DOI: 10.1007/s00062-011-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repositioning of a Pipeline Embolization Device Dislocated from the Vertebral into the Basilar Artery Using a Stent-in-Stent Technique

Abstract: Repositioning of a lost PED is feasible using a stent-in-stent technique. Principally, dislodgement force is higher using a larger PED, while in this case care has to be taken to avoid incidental extraction of the second PED out of the microcatheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The authors described that, in both patients, the PEDs migrated up to 3.3 mm distally as early as 2 weeks after deployment, even with the use of the anchoring overlapping stent 23. Intracranial migration of a PED has previously been described in the literature and appears to be relatively infrequent 19 24 25. Cohen et al 26 compared the Silk stent and a PED in intracranial applications and observed frequent migration of the Silk stent and no cases of PED migration.…”
Section: Discussionmentioning
confidence: 96%
“…The authors described that, in both patients, the PEDs migrated up to 3.3 mm distally as early as 2 weeks after deployment, even with the use of the anchoring overlapping stent 23. Intracranial migration of a PED has previously been described in the literature and appears to be relatively infrequent 19 24 25. Cohen et al 26 compared the Silk stent and a PED in intracranial applications and observed frequent migration of the Silk stent and no cases of PED migration.…”
Section: Discussionmentioning
confidence: 96%
“…Different techniques have been described to solve PED migration, including open surgery,7 snare assisted rescue,2 3 balloon anchoring for distal end herniation,8 or stent-in-stent techniques 4. While distal end PED migration allows more endovascular rescue options, a proximal end migration requires more complex maneuvers to regain distal access through the stent, such as the presented case 2–4.…”
Section: Discussionmentioning
confidence: 98%
“…Proximal migration of PEDs has been described in cases of placement within both anterior and posterior circulations [48][49][50][51][52][53][54][55] . Spontaneous shortening of PEDs has also been described [56] .…”
Section: Discussionmentioning
confidence: 99%